Applicability of Meditative Techniques in the Educational Institutions - Viktorija Rubčić; Ivica Kelam (Pannoniana, 2021)
The purpose of this paper is to explore different meditative techniques and their benefits and to open a discussion on the applicability of meditative techniques in educational institutions. Thus, the ability to apply meditative techniques to help develop self-control and regulation of emotions, as well as a form of prevention of problematic behavior in children. Upbringing begins in the family, and this is where the foundations for building a child’s personality are formed. The social community and the environment surrounding us contribute to what we will become. Different religions have their upbringing principles, and given the origin of meditation, we will explore the possibility of its application in spiritual upbringing. This paper will show some meditation techniques and their connection with emotions, how they can help children, as well as the positive aspects of applying meditative techniques in various dysfunctional behaviors. We will explore how and in what way meditation techniques are applied in the world and how and where the application of meditative techniques occurs in children in Croatia.